Required to work from home: examining transitions to digital communication channels during the COVID-19 pandemic. Issue 1 (1st January 2022) - McGloin, Rory; Coletti, Amanda; Hamlin, Emily; Denes, Amanda
ABSTRACT: This study examined how the COVID-19 pandemic and related work-from-home (WFH) mandates impacted the use of computer-mediated communication (CMC) channels in the workplace and how the use of CMC channels influenced the perceived quality of supervisory relationships. A survey was administered during spring 2020 to a sample of U.S. employees required to work remotely due to COVID-19. The findings indicated a significant relationship between the use of text messaging and rapport, a signal that the building or maintaining of interpersonal rapport in today's workplace may require more personal (and less formal/traditional) channels of communication. The results also revealed that employees with higher levels of CMC apprehension had lower rapport with their supervisors. The findings have implications for organizations that may have moved (or will move) to more remote work settings, and suggestions are offered for mitigating the impact of CMC-only interactions on supervisory relationships.